Becoming-Data, Becoming-Mountain - Mark Nunes (Journal of the Austrian Association for American Studies, 2021)
This article explores our ecological relation to both information and information technologies as we "mediate mountains." Starting with a Gibsonian approach to affordances, and considering how an agent-specific account of action limits human access to "the digital," I suggest that the interface between human and device marks a double-coupling of two agents—one digital the other embodied—each of which draws out the other to alter potential action. The essay explores the affordances of agents and the environments in which they act, and how action seemingly occurs across the boundaries marked by the human-device interface. Drawing on actor network theory, assemblage theory, and Don Ihde's "inter-relational ontology," I examine how, within an ecology of humans and mobile devices, "agency" and "action" operate within a Deleuzean transversal, cutting across body-machine boundaries. As an application of this analysis, I examine the relationship between embodied and digital agents "in the wild" of the mountains, through AR and GPS-enabled smartphone apps, and how each agent, acting upon its own environment, gives rise to transversal events that alter the affordances offered to agents across a seemingly uncrossable divide.